Association of hospital admission and forced vital capacity endpoints with survival in patients with idiopathic pulmonary fibrosis: analysis of a pooled cohort from three clinical trials. Issue 5 (May 2015) - Durheim, Michael T; Collard, Harold R; Roberts, Rhonda S; Brown, Kevin K; Flaherty, Kevin R; King, Talmadge E; Palmer, Scott M; Raghu, Ganesh; Snyder, Laurie D; Anstrom, Kevin J; Martinez, Fernando J
Summary: Background: Mortality is an impractical primary endpoint for clinical trials in patients with idiopathic pulmonary fibrosis who have mild-to-moderate physiological impairment because event rates are low. Change in forced vital capacity (FVC) is widely accepted as a surrogate for mortality and is the most common primary endpoint in clinical trials for this disorder. Use of hospital admission as a predictor for mortality, independent of FVC decline, has not been well defined. We aimed to ascertain the independent and combined association of hospital admission and at least a 10% decrease in FVC with all-cause mortality. Methods: We did a pooled cohort study of 517 patients with idiopathic pulmonary fibrosis from three IPFnet multicentre randomised controlled trials. We compared the incidence of non-elective hospital admission and a 10% or greater reduction in FVC across strata of baseline physiological impairment. We used Cox proportional-hazards models to assess the risk of all-cause mortality associated with these surrogate events, occurring up to a predefined landmark timepoint. The three studies are registered atClinicalTrials.gov, numbersNCT00650091, NCT00517933, andNCT00957242 . Findings: Seven patients died before the landmark timepoint. Of the 510 patients remaining, 38 (7%) were admitted to hospital up to the predefined timepoint and 58 (11%) had a categorical decrease in FVC of at least 10%. Most patients admitted to hospital did not have a 10% or greater decrease in FVC (30 vs eight). Both surrogate events were associated with subsequent time to death from any cause (hazard ratio [HR] for admission 4·05, 95% CI 1·36–12·11 vs HR for 10% or greater decline in FVC 4·68, 1·83–11·99). When causes of hospital admission were considered, only respiratory events were associated with mortality (5·97, 1·81–19·74). Interpretation: Hospital admission might be an appropriate component of a clinically meaningful composite endpoint that improves the feasibility of clinical trials in idiopathic pulmonary fibrosis. Further studies are needed to refine the most appropriate definition of hospital admission for future trials. Funding: US National Heart, Lung, and Blood Institute (NHLBI), and The Cowlin Family Fund at the Chicago Community Trust.